Crass struggle : glitz, greed, and gluttony in a wanna-have world - Naylor, R. T., 1945- (McGill-Queen's University Press, 2011)
Through a series of outrageous but all too true stories, this book reveals the appalling consequences of consumerism run amok and its links to repetitive financial swindles and the alarming degradation of the biophysical environment.